HUBUNGAN ANTARA PELATIHAN DAN PENGEMBANGAN KARIR DENGAN KEPUASAN KERJA KARYAWAN PADA PT. ISS INDONESIA - Susi Marni; Julisman; Rosmawati Agustini (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This study analyzes the relationship between training and career development with job satisfaction. The method used for sampling in this study is a survey. The sample used is 53 respondents who are employees of PT ISS Indonesia area of ​​PT. Chiba Vision Batam. The data collection technique uses a questionnaire technique. While the analysis of the data using quantitative analysis. The research results obtained partially or simultaneously both independent variables affect the dependent variable. So it can be concluded that there is a relationship between training and career development in increasing job satisfaction, this is because the R value is 0.763 or 76.3%. Furthermore, judging from the Pearson bivariate correlation value, the sig value of the training variable with job satisfaction is 0.000 <0.005, which means that there is a significant correlation or relationship between training and job satisfaction. The career development variable with job satisfaction has a sig value of 0.000 <0.005, which means that there is a significant correlation or relationship between career development and job satisfaction